Sustainable Green Processes Enabled by Pulse Electrolytic Principles. (September 2020) - Hall, Timothy D.; Inman, Maria E.; Taylor, E. Jennings (EJ)
Abstract : Electrochemical and solid state science, engineering, and technology have an important role to play in society's sustainable future. Early discussions of the potential environmental contributions by academic, government, and industrial electrochemists were presented in Electrochemistry of Cleaner Environments (1972), Electrochemistry for a Cleaner Environment (1992), and Environmental Aspects of Electrochemical Technology (2000). Some important electrochemical technologies include batteries and fuel cells for mobile (electric vehicle) power and stationary energy storage (wind, solar), conversion and capture of greenhouse (carbon dioxide) gases, contaminate destruction (PFAS), and electrochemical recycling of electronics in support of a circular economy among others. Additionally, many have noted that electrochemical processes are inherently environmentally friendly as "electrons are green." While we agree with this notion, we also note that many electrochemical processes based on direct current (DC) electrolysis, such as electrodeposition (plating) and surface finishing (electropolishing and electrochemical machining), use environmental and worker "unfriendly" electrolytes. By altering the electrochemical paradigm from one based on DC electrolysis to one based on pulse/pulse reverse current (P/PRC) electrolytic principles, simpler electrolytes with favorable manufacturing/worker and environmental impacts may be accrued. After a brief introduction to the author's perspective, we present examples of sustainable technologies enabled by P/PRC electrolysis: 1) green electrodeposition of chromium for functional applications, 2) worker friendly electropolishing of niobium for particle accelerator applications, and 3) zero-discharge electrochemical machining of cannon barrels.